Maxillomandibular giant osteosclerotic lesions - Constantino LEDESMA-MONTES; María Dolores JIMÉNEZ-FARFÁN; Juan Carlos HERNÁNDEZ-GUERRERO (University of São Paulo, 2018)
Abstract Giant Osteosclerotic Lesions (GOLs) are a group of rarely reported intraosseous lesions. Their precise diagnosis is important since they can be confused with malignant neoplasms. Objective This retrospective study aimed to record and analyze the clinical and radiographic Giant Osteosclerotic Lesions (GOLs) detected in the maxillomandibular area of patients attending to our institution. Materials and Methods: Informed consent from the patients was obtained and those cases of 2.5 cm or larger lesions with radiopaque or mixed (radiolucid-radiopaque) appearance located in the maxillofacial bones were selected. Assessed parameters were: age, gender, radiographic aspect, shape, borders, size, location and relations to roots. Lesions were classified as radicular, apical, interradicular, interradicular-apical, radicular-apical or located in a previous teeth extraction area. Additionally, several osseous and dental developmental alterations (DDAs) were assessed. Results Seventeen radiopacities in 14 patients were found and were located almost exclusively in mandible and were two types: idiopathic osteosclerosis and condensing osteitis. GOLs were more frequent in females, and in the anterior and premolar zones. 94.2% of GOLs were qualified as idiopathic osteosclerosis and one case was condensing osteitis. All studied cases showed different osseous and dental developmental alterations (DDAs). The most common were: Microdontia, hypodontia, pulp stones, macrodontia and variations in the mental foramina. Conclusions GOLs must be differentiated from other radiopaque benign and malignant tumors. Condensing osteitis, was considered an anomalous osseous response induced by a chronic low-grade inflammatory stimulus. For development of idiopathic osteosclerosis, two possible mechanisms could be related. The first is modification of the normal turnover with excessive osseous deposition. The second mechanism will prevent the normal bone resorption, arresting the osseous breakdown process.